In Vitro Susceptibility and Florfenicol Resistance in Citrobacter Isolates and Whole-Genome Analysis of Multidrug-Resistant Citrobacter freundii. (19th November 2019) - Zhou, Wangxiao; Chen, Qianqian; Qian, Changrui; Shen, Kai; Zhu, Xinyi; Zhou, Danying; Lu, Wei; Sun, Zhewei; Liu, Hongmao; Li, Kewei; Xu, Teng; Bao, Qiyu; et al.
Abstract : The genus Citrobacter is an opportunistic pathogen causing infections in animals, and the published data for its resistance to florfenicol are scarce. In this study, we investigated the antimicrobial susceptibility and molecular characteristics of florfenicol resistance genes among Citrobacter isolates from animal and relevant environmental samples and conducted a comparative analysis of a multidrug-resistant Citrobacter freundii strain isolated from a rabbit. Among 20 Citrobacter strains isolated from animal samples, resistance was most commonly observed to ampicillin (100%), tetracycline (75%), streptomycin (65%), florfenicol (60%), chloramphenicol (60%), and aztreonam (50%), while all the strains found in environmental samples were resistant to few antibiotics. The florfenicol resistance gene floR was detected in 12 isolates (48%, 12/25) from animal samples, and all of the floR -positive isolates were resistant to florfenicol with minimum inhibitory concentration (MIC) values ≥256  μ g/mL. Sequencing and comparative analysis of the plasmids from a multidrug-resistant C. freundii isolate named R47 showed that the floR -containing region in the plasmid pR47-54 was a truncated transposon-like structure and could be found on both plasmids and chromosomes of bacteria of either animal or human origin. Furthermore, a range of antimicrobial and metal resistance genes associated with mobile genetic elements could be identified in pR47-54 and the other plasmid pR47-309 of C. freundii R47. These results provide in-depth views into the phenotypic and molecular characteristics of Citrobacter isolates recovered from animal and relevant environmental samples, as well as highlight the role horizontal gene transfer plays in the dissemination of plasmid-encoded resistance genes.